Dinamika Pendidkan Islam di Indonesia: Kajian Historis dari Era–Pra Kolonial Hingga Reformasi - Nurfadillah; Siti Nur Hidayah; Idrus L (CV Edujavare Publishing, 2026)
This study examines the historical periodization of Islamic education in Indonesia from the pre-colonial era to the Reformation era. This study is motivated by the dynamics of Islamic education development, which has constantly changed along with social, political, and cultural developments in each historical period. This study aims to analyze the development of Islamic education and the factors influencing changes in the system, institutions, and policies of Islamic education in Indonesia. This study uses a qualitative approach with library research. Data were obtained through documentation studies from various sources, such as books, scientific journal articles, and official documents relevant to the research topic. Data analysis techniques were descriptive-analytical through the stages of data reduction, data presentation, and conclusion drawing. The results show that Islamic education in Indonesia developed dynamically and adaptively to social and political changes in each historical period. In the pre-colonial era, Islamic education developed through mosques, surau (Islamic boarding schools), and Islamic boarding schools (pesantren). During the colonial period, Islamic education experienced both marginalization and institutional modernization. Meanwhile, in the Reformation era, Islamic education was strengthened through educational decentralization policies, the transformation of IAIN into UIN, and formal recognition of Islamic boarding schools through national regulations.